A comparative clinical study of the efficacy of subepithelial connective tissue graft and acellular dermal matrix graft in root coverage: 6-month follow-up observation - Libby John Thomas; Pamela Emmadi; Ramakrishnan Thyagarajan; Ambalavanan Namasivayam (Wolters Kluwer Medknow Publications, 2013)
Aims: The purpose of this study was to compare the clinical efficacy of subepithelial connective tissue graft and acellular dermal matrix graft associated with coronally repositioned flap in the treatment of Miller's class I and II gingival recession, 6 months postoperatively. Settings and Design: Ten patients with bilateral Miller's class I or class II gingival recession were randomly divided into two groups using a split-mouth study design. Materials and Methods: Group I (10 sites) was treated with subepithelial connective tissue graft along with coronally repositioned flap and Group II (10 sites) treated with acellular dermal matrix graft along with coronally repositioned flap. Clinical parameters like recession height and width, probing pocket depth, clinical attachment level, and width of keratinized gingiva were evaluated at baseline, 90 th day, and 180 th day for both groups. The percentage of root coverage was calculated based on the comparison of the recession height from 0 to 180 th day in both Groups I and II. Statistical Analysis Used: Intragroup parameters at different time points were measured using the Wilcoxon signed rank test and Mann-Whitney U test was employed to analyze the differences between test and control groups. Results: There was no statistically significant difference in recession height and width, gain in CAL, and increase in the width of keratinized gingiva between the two groups on the 180 th day. Both procedures showed clinically and statistically significant root coverage (Group I 96%, Group II 89.1%) on the 180 th day. Conclusions: The results indicate that coverage of denuded root with both subepithelial connective tissue autograft and acellular dermal matrix allograft are very predictable procedures, which were stable for 6 months postoperatively.